RECORDING THE HARVEST, CULTIVATING THE FUTURE THROUGH SUSTAINABILITY ACCOUNTING IN CLOVE FARMING - Hasnidar Hasnidar; Vina Olivia Pebrianty; La Ode Muhammad Arfan Samrin; Taufan Sufatriansa Awal; Dzulkifli Abdillah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to identify the practices of recording and managing the financial results of clove farming, analyze the challenges in implementing sustainability accounting, and propose a simple record-keeping model based on sustainability accounting principles to support the sustainability of farming activities. The research employs a qualitative descriptive method with a case study approach, collecting field data through observation, interviews, questionnaires, and documentation. Data were analyzed thematically to reveal recording patterns, encountered problems, and opportunities for implementing sustainability accounting. The findings show that clove farming in Puu Lawulo Village has significant potential; however, harvest timing and weather conditions greatly influence yield and quality. Farmers’ accounting practices remain simple and seasonal, with no separation between household and farm finances, and without recording biological assets or environmental data. The main obstacles include low accounting literacy, limited access to digital tools, fluctuating clove prices, and the absence of practical recording formats—resulting in financial and environmental management that is still carried out intuitively, without analytical support for sustainability. Therefore, to enhance the effectiveness and sustainability of clove farming, it is necessary to implement a simple and adaptive sustainability accounting model. This study proposes a chart of accounts (COA) framework that includes income, direct costs, agronomy, occupational health and safety (OHS), and assets.